Use of cesium-137 as a radiotracer in the quantification of tropical soil erosion - Rita Y. Sibello Hernández (Nucleus, 2005)
The main objective of this work was to evaluate the app!icability of this technique to quantify the soil erosion in the tropical region. With this purpose the technique was applied in the tropical soils belonging to a glide parcel, in Cienfuegos province, in Cuba, in the Caribbean area. This allowed us to compare and to demonstrate the good agreement of the results of the soilloss quantification obtained using the 137CS technique: 37.00:f: 0.80 t.ha-1.year' with the obtained using erosion plots in the Soil Experimental Station in Barajagua: 40 t.ha-1. year'.